2022
DOI: 10.1002/jbt.23168
|View full text |Cite
|
Sign up to set email alerts
|

Protective activity of purpurin against d‐galactosamine and lipopolysaccharide‐induced hepatorenal injury by upregulation of heme oxygenase‐1 in the RBC degradation cycle

Abstract: Acute liver failure, associated with oxidative stress and sustained inflammation is the major clinical manifestation of liver diseases with a high mortality rate due to limited therapeutic options. Purpurin is a bioactive compound of Rubia cordifolia that has been used in textile staining, as a food additive, and as a treatment of multiple chronic and metabolic diseases associated with inflammation and oxidative stress. The present work aimed to investigate the protective efficacy of purpurin against hepatoren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…Both type 1 and type 2 diabetes play a crucial role in renal failure, whereas it is more prevalent in type 2 diabetes patients. 20, 31 Antiglycemic and antihypertensive drugs, such as ACE inhibitors, Angiotensin II receptor blockers, were not so potent and still, and the incidence of diabetic nephropathy remains increasing. Most of the discovered drugs failed during the clinical Phase III trials, 32, 33 hence it is necessary to discover a potent drug to ameliorate diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both type 1 and type 2 diabetes play a crucial role in renal failure, whereas it is more prevalent in type 2 diabetes patients. 20, 31 Antiglycemic and antihypertensive drugs, such as ACE inhibitors, Angiotensin II receptor blockers, were not so potent and still, and the incidence of diabetic nephropathy remains increasing. Most of the discovered drugs failed during the clinical Phase III trials, 32, 33 hence it is necessary to discover a potent drug to ameliorate diabetic nephropathy.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study revealed that purpurin effectively ameliorated hepatotoxicity, 29 suppressed atopic dermatitis, 30 protected hepatorenal injury, 31 and demonstrated neuroprotective effects 32 in various study models.…”
Section: Introductionmentioning
confidence: 99%